Economic significance of commodity return forecasts from the fractionally cointegrated VAR model - Sepideh Dolatabadi; Paresh Kumar Narayan; Morten Ørregaard Nielsen; Ke Xu (Queen's University, Department of Economics, 2015)
Based on recent evidence of fractional cointegration in commodity spot and futures markets, we investigate whether a fractionally cointegrated model can provide statistically and/or economically significant forecasts of commodity returns. Specifically, we propose to model and forecast commodity spot and futures prices using a fractionally cointegrated vector autoregressive model that generalizes the more well-known cointegrated vector autoregressive model to allow fractional integration. We derive the best linear predictor forecast for this model and perform an out-of-sample forecast comparison with forecasts from the more standard (non-fractional) model. In our empirical analysis to daily data on 15 commodity spot and futures markets, the fractional model is found to be superior in terms of in-sample fit and also out-of-sample forecasting based on statistical metrics of forecast comparison. We then analyze the economic significance of the forecasts through a dynamic trading strategy based on a portfolio with weights derived from a mean-variance utility function. This analysis leads to statistically significant and economically meaningful pro.ts in the commodity markets, and also shows that the fractional model generates higher profits on average compared with the non-fractional model.
Keywords: C32; G11; 330; commodity markets; economic significance; forecasting; fractional cointegration; futures markets; price discovery; vector error correction model